Assessing the Relevance of Spirituality and Corporate Social Responsibility in A Family Business: A Scooping Review - Sulis Rochayatun; Heri Pratikto; Cipto Wardoyo; Puji Handayati; Rosmiza Bidin (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
Previous literature review studies have explored the implementation of social responsibility in family companies, while literature reviews that focus explicitly on the spirituality of family business in the implementation of social responsibility have not been found. The purpose of this scoping review is to map out studies that assess the spirituality of family business in the implementation of social responsibility. The scoping review of this study follows the five main stages outlined by Arkset and O'Malley (2005). The steps taken are (1) identifying research questions; (2) identify relevant studies; (3) selection of relevant studies; (4) mapping data; (5) Compile, summarize and report the results. The studies reviewed were selected from three electronic databases, namely: Emerald, Springer and Taylor & Francis within a period of 12 years from 2012-2021. The results of the scoping review show that most studies acknowledge that spirituality in family establishments is stronger. Social responsibility decisions and policies are considered as ethical decisions that involve the influence of religion and spirituality as the basis for decision making. The spiritual values that are built in family business can be the basis for the implementation of social responsibility that is oriented to the long-term goal of corporate sustainability. The theoretical implication of this research is to provide additional literature on CSR in family companies in terms of spirituality so that it can be a guide for future research. Keywords: Corporate Social Responsibility, Spirituality, Family Business, Scooping Review